A decade of flowering phenology of the keystone saguaro cactus (Carnegiea gigantea). Issue 2 (21st February 2019) - Renzi, Julianna J.; Peachey, William D.; Gerst, Katharine L.
Abstract : Premise of the Study: Phenology is the study of biological life cycle events, such as flowering and migration. Climate patterns can alter these life history events, having ecosystem‐wide ramifications. For example, warmer springs are associated with earlier leaf‐out for many species, impacting species interactions and growing‐season carbon dynamics. While phenological research has been conducted extensively in temperate regions, relatively little is known about the phenological responses in arid and semi‐arid regions. Methods: In this study we looked at the flowering phenology of a keystone species in the Sonoran Desert, the saguaro cactus ( Carnegiea gigantea ). The timing and abundance of flowering was observed on 151 individuals for 10 years at a site near Tucson, Arizona, USA. Using six phenological traits, we explored the relationship between saguaro size and flowering and the climatic drivers of flowering. Key Results: Our analyses demonstrated how the calculation of phenological traits at the individual versus the population level can yield differing responses to climate variability, suggesting that not all studies examining the same trait (e.g., first day of bloom) are directly comparable. We found that larger cacti began flowering earlier, flowered for longer, and produced more flowers. Warmer temperatures were correlated with advanced onset and higher bloom yields, while increased precipitation appeared to delay onset and reduce bloom yields. Conclusions: Given that climate models predict that the Southwestern USA will become increasingly warmer with more variable precipitation, saguaros may begin flowering earlier in the season and flower more intensely, which could impact pollen availability and population dynamics.